THE PROPORTION OF PATIENTS WITH HYPERTENSION IN THE GROUPS OF TERMS PROLONGED QTc INTERVALS PER DAY DATA OF AMBULATORY ECG MONITORING IN DEPENDENCE FROM CLINICAL SIGNS - Tselik, N. E.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
The study of the proportion of patients in 82 patients with hypertension in groups of different periods of prolonged QTc per day was performed based on the data of the AM of the ECG, depending on the clinical signs. Depending on the duration of prolonged QTc per day, the patients were assigned to one of three groups: group 1 – the term extended by day of the interval QTc from 0 to 33.3 %, group 2 – from 33.4 to 66.6 %, group 3 – from 66.6 to 100 %. The proportion of patients with hypertension was determined in the groups of the prolonged QTc interval depending on age, sex, weight of patients, type of circadian heart rate index, stage, degree and prescription of EH, presence of coronary heart disease, FC and stage of CHF and diabetes mellitus. According to the AM ECG, an prolonged QTc interval occurs in each patient with hypertension, with an increase of 0 to 33.3 % per day, it is detected in 76 %, from 33.4 to 66.6 % – in 16 % and with 66.7 to 100 % – in 8 % of patients. The existence of a prolonged QTc interval in each patient indicates that in its analysis it is necessary to base on the data of the AM of the ECG taking into account, except for the elongation and lengthening for a day.